1994
DOI: 10.21273/jashs.119.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Antioxidants in Apple Peel as Related to Preharvest Factors and Superficial Scald Susceptibility of the Fruit

Abstract: Antioxidants are believed to protect against the oxidation of α-farnesene to conjugated trienes in apple (Malus domestica, Borkh.) peel, thus providing resistance against superficial scald development. We conducted three experiments in which apples were a) harvested weekly, during which they were exposed to increasing hours at <10C during ripening; b) induced to ripen with no hours at <10C by applying ethephon; and c) enclosed in paper bags as they ripened. Inducing rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…A number of antioxidants have absorption maxima near 200 nm (Anet, 1974), and these values correlated strongly with assays of lipid-soluble antioxidant activity of apple peel extracts (Meir and Bramlage, 1988). While the results suggest that higher temperatures and warming may have reduced the formation of conjugated trienes by increasing endogenous antioxidants, Barden and Bramlage (1994b) found that 0D 200 nm values can increase with fruit ripening without corresponding increases in the principal lipid-soluble antioxidants in fruit peel. Therefore, the 0D 200 nm values recorded in peel extracts may not be reliable indices of antioxidant concentrations.…”
Section: Discussionmentioning
confidence: 82%
“…A number of antioxidants have absorption maxima near 200 nm (Anet, 1974), and these values correlated strongly with assays of lipid-soluble antioxidant activity of apple peel extracts (Meir and Bramlage, 1988). While the results suggest that higher temperatures and warming may have reduced the formation of conjugated trienes by increasing endogenous antioxidants, Barden and Bramlage (1994b) found that 0D 200 nm values can increase with fruit ripening without corresponding increases in the principal lipid-soluble antioxidants in fruit peel. Therefore, the 0D 200 nm values recorded in peel extracts may not be reliable indices of antioxidant concentrations.…”
Section: Discussionmentioning
confidence: 82%
“…The effect of ripening stage on the α‐tocopherol content of 5 varieties of olives was reported by Garcia et al76 Verdial and Villalonga varieties exhibited a significant decrease in α‐tocopherol content as ripening progressed, whereas no significant effects of ripening on α‐tocopherol content were observed in Blanqueta, Arbequina and Lechin varieties. In apples, both induced ripening with ethephon and delayed harvesting increased α‐tocopherol content in the peel, while bagging the fruit before ripening decreased α‐tocopherol 77…”
Section: Plant Food Sourcesmentioning
confidence: 99%
“…But even 'Granny Smith' becomes less prone to scald when allowed to achieve full maturity before harvest. Delayed harvest increases the concentrations of α-tocopherol and carotenoids, but not ascorbic acid, and greatly reduces scald development (Barden and Bramlage, 1994c). Ethephon (2-chloroethylphosphonic acid), an ethylene-generating chemical, hastens ripening and reduces scald (Couey and Williams, 1973;Greene et al, 1977;Hammett, 1976;Lurie et al, 1989b;Windus and Shutak, 1977).…”
Section: Characteristics and Manifestations Of Scaldmentioning
confidence: 99%